Historical inputs of polycyclic aromatic hydrocarbons in the preserved tropical estuary of the Itapicuru River, Bahia, Brazil. (July 2020) - Guimarães, Lucas Medeiros; De França, Elvis Joacir; de Arruda, Gilberto Nascimento; Albergaria-Barbosa, Ana Cecília Rizzatti de
Abstract: The aim of present study was to evaluate temporal changes in the distribution of polycyclic aromatic hydrocarbons (PAHs) in the estuary of the Itapicuru (Brazil). A sediment core was sampled in the study area. Concentrations of the 16 priority PAHs were analyzed using gas chromatography coupled to a mass spectrometry. A gas flow proportional counter was used to estimate the sedimentation rate through the determination of 210 Pb. Granulometric fractions and total organic carbon (TOC) concentrations were also evaluated. Concentrations of TOC and PAHs ranged from 0.65 to 2.51% and 1.98 to 43.1 ng g −1 (dry weight), respectively. Significant correlations ( p < .05) were found between the mud content in the sediment core samples and concentrations of both TOC and PAHs. Higher PAH concentrations occurred after the 1950s. The main sources of PAHs over time were local human activities on the northern coast of the state of Bahia. Graphical abstract: Unlabelled Image Highlights: First study of contamination by PAHs in the estuary of the Itapicuru river This study can be used as baseline to verify the impact of the 2019 oil spill The area studied has a low degree of contamination Local activities are the main sources of PAHs in the estuary